PEMANFAATAN DIMENSI SETTLING POND UNTUK PENURUNAN PENCEMARAN KIMIA-FISIK AIR LIMBAH PERTAMBANGAN BATUBARA - Saibun Sitorus (PROSIDING SEMINAR KIMIA, 2020)
The use of settling pond dimensions in coal mining has been widely used to reduce chemical-physical pollution of wastewater. This study aims to take advantage of the dimensions of the settling pond in wastewater pollutants based on quality and to see the comparison of the actual load of wastewater with the maximum pollutant load in the settling pond location. The method in this research is descriptive qualitative. The sampling location consisted of 3 stations, namely the settling pond location 1, location 2 and location 3. The results showed that the decrease in the settling pond in treating mining wastewater based on chemical-physical parameters can reduce the pollutant load by 2% (0.0031 kg/second) for the settling pond location 1.21% (0.4281kg/second) for location 2 and 1% (0.0074 kg/second) for location 3.The actual pollutant load of wastewater, physical and chemical parameters are smaller than the pollutant load maximum (CPA<BPM). Actual pollutant load (BPA) of settling pond location 1 is 0.107 kg/second, location 2 is 0.032 kg/second and location 3 is 0.105 kg/second. Meanwhile, the maximum pollutant load (BPM) of settling pond for location 1 is 0.165 kg/second, location 2 is 2.01 kg/second and location 3 is 0.628 kg/second. Decreasing pollutant load in settling ponds. Several factors include vegetation, distance between the source of pollutants (catchment area) and the settling pond, dimensions of the settling pond (retention pond), the process of coagulant application, topography, type of lithology. Keywords : Settling pond, pollution reduction, pollutant load, chemical-physical